2003
DOI: 10.1084/jem.20021836
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin (IL)-15Rα–deficient Natural Killer Cells Survive in Normal but Not IL-15Rα–deficient Mice

Abstract: Natural killer (NK) cells protect hosts against viral pathogens and transformed cells. IL-15 is thought to play a critical role in NK cell development, but its role in the regulation of peripheral NK cells is less well defined. We now find that adoptive transfer of normal NK cells into mice lacking the high affinity interleukin (IL)-15 receptor, IL-15Rα, surprisingly results in the abrupt loss of these cells. Moreover, IL-15Rα–deficient NK cells can differentiate successfully in radiation bone marrow chimera b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
211
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(223 citation statements)
references
References 45 publications
10
211
1
1
Order By: Relevance
“…Analyses of both IL-15-deficient and IL-15 receptor (IL-15R)-deficient mice have demonstrated that this cytokine promotes the differentiation of NK-cell precursors (CD122 + NK1.1 − cells) into immature NK cells (CD122 + NK1.1 + cells), and have additionally suggested that IL-15 also operates at the slightly later stages of NK-cell maturation during which TAM signalling is required [77][78][79][80][81] . It is therefore interesting that a physical and physiological association between the TAM receptor AXL and the α-subunit of the IL-15R has been demonstrated 82 .…”
Section: Tam Control Of Natural-killer-cell Differentiationmentioning
confidence: 99%
“…Analyses of both IL-15-deficient and IL-15 receptor (IL-15R)-deficient mice have demonstrated that this cytokine promotes the differentiation of NK-cell precursors (CD122 + NK1.1 − cells) into immature NK cells (CD122 + NK1.1 + cells), and have additionally suggested that IL-15 also operates at the slightly later stages of NK-cell maturation during which TAM signalling is required [77][78][79][80][81] . It is therefore interesting that a physical and physiological association between the TAM receptor AXL and the α-subunit of the IL-15R has been demonstrated 82 .…”
Section: Tam Control Of Natural-killer-cell Differentiationmentioning
confidence: 99%
“…12 IL-15 and IL-15Ra are necessary for the differentiation of NK cells from lymphoid precursors and for their steady-state survival. 13,15,16 IL-15 is mitogenic for NK cells, enhances secretion of pro-inflammatory cytokines and upregulates their cytolytic machinery. 12,17 The multimeric receptor for IL-15 encompasses two signaling subunits IL-2Rb (CD122) and IL-2Rg (CD132), while the high-affinity specific chain (IL-15Ra) makes limited or no contribution to signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Because IL-15R␣ Ϫ/Ϫ mice lack NK cells (26), we used IL-15R␣-deficient chimeric mice in which bone marrow from IL-15R␣-deficient mice was used to reconstitute irradiated wt recipients. In these chimeric mice, host cells expressing IL-15R␣ efficiently present IL-15 in trans to IL-15R␣-null NK cells promoting their development and survival (29,35).…”
Section: Impact Of Il-15r␣ On Nk Cells In Modulating Selective Prolifmentioning
confidence: 99%
“…IL-15R␣-deficient chimeric mice were generated, as previously described (35). Briefly, bone marrow was harvested from IL-15R␣ Ϫ/Ϫ mice that had been backcrossed to B6 mice for at least eight generations or from wildtype (wt) B6 mice.…”
Section: Il-15r␣-deficient Chimeric Micementioning
confidence: 99%